PERENCANAAN PROGRAM MOTIVASI BANGUN DARI MIMPI BUKAN BERARTI TIDAK BISA BERMIMPI KEMBALI - Halalah Amaliyah; Isnani Nurpazriah; Nur Fadiyah Khaerunnisa; Ridha Syahnai; Shofin Muhammad; Yuli Sri Awaliyah (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
The Center for Community Learning Activities (PKBM) is a non-formal educational institution that organizes several programs, one of which is the equality program or pursuing packages. Package A is equivalent to SD, Package B is equivalent to SMP, and Package C is equivalent to SMA. Non-formal education has a function as a substitute, complement, and enhancer. Motivation can be defined as something within oneself that drives activities to achieve certain goals. a Motivational Talk Show program with the theme